An Experimental Study on The Impact of Digital Multilingual Thematic Dictionary for The Sixth Grade Students’ Literacy Skill - Ketut Ayu Swati Pramitha Yuliandari; Ni Made Ratminingsih; I Gede Budasi (Acitya: Journal of Teaching and Education, 2023)
This research aims to present justification for whether or not there is any significant impact of using a digital multilingual thematic dictionary on sixth-grade students’ literacy skills using quasi-experimental research with a pre-test and post-test only control group design. The researcher determined the research sample using statistical matching scores proposed by Fraenkel et al. (2012). The statistical matching scores were administered in determining the two intact groups. Two intact groups which had similar scores and were statistically proven to have insignificant differences in abilities were selected as the research sample, namely; (1) SD N 1 Kubutambahan was the control group, and (2) SD N 3 Banjar Jawa was the experimental group. The instruments used in this research were literacy skill tests which contain pre-test and post-test questions, and teaching scenarios for the control and experimental group. The pre-test was given before treatment and the post-test was given after treatment. Both groups received three times of treatments with three materials namely home activities, animals, and public places. The obtained data were analyzed quantitatively with descriptive statistical, inferential statistical, and N-Gain score test analysis. Based on the results of the calculation of the N-Gain Score test and the descriptive analysis, the mean score of the N-Gain for the experimental group was 73.3759%, while the mean score of the N-Gain for the control group was 48.0249%. The results of the N-Gain score test show that the use of the digital multilingual thematic dictionary in the experimental group was moderately effective, while the use of the printed thematic picture dictionary in the control group was less effective. Thus, it can be concluded that the digital multilingual thematic dictionary performs better than a printed thematic picture dictionary on sixth-grade students’ literacy skills.